Autophagy in tumor immune escape and immunotherapy - Huan Wang; Peng Sun; Xijing Yuan; Zhiyong Xu; Xinyuan Jiang; Mingshu Xiao; Xin Yao; Yueli Shi (Molecular Cancer)
Abstract The immunotherapy targeting tumor immune escape mechanisms has become a critical strategy in anticancer treatment; however, the challenge of immune resistance remains significant. Autophagy, a cellular response to various stressors, involves the degradation of damaged proteins and organelles via lysosomal pathways, maintaining cellular homeostasis. This process not only supports tumor cell survival but also profoundly impacts the efficacy of cancer immunotherapies. The modulation of autophagy in tumor cells or immune cells exerts dual effects on tumor immune escape and immunotherapy. However, the mechanistic details of how autophagy influences the immune system and therapy remain inadequately understood. Given this complexity, a deeper understanding of the role of autophagy in the tumor-immune landscape could reveal novel therapeutic avenues. By manipulating autophagy appropriately, it may be possible to overcome immune resistance and enhance the effectiveness of immunotherapeutic strategies. This article summarizes the role of autophagy in tumor immunity, its relationship with immunotherapy, and the potential therapeutic benefits of targeting autophagy to strengthen antitumor immune responses and optimize the outcomes of immunotherapy.